The office on missing persons in Sri Lanka: why truth is a radical proposition - Kodikara, Chulani (International journal of transitional justice, 2023)
In 2016, the Sri Lanka Parliament passed the Office on Missing Persons Act (OMP) ‘to search for and trace missing persons.’ At the time, Sinhala Buddhist nationalist leaders strongly objected to it. In this article, I read their resistance as resistance to a truth-seeking mechanism. Locating my analysis within a global paradigm of ‘dealing with the past’ through truth-seeking that assumes that ‘truth is easier than justice,’ I show that nationalist resistance to the OMP flies in the face of this assumption. In postwar Sri Lanka, truth is not just a second-best option to justice but an equally radical demand. However, I also show that those same resistors have maintained the OMP on returning to power for several different reasons. Finally, I explore the response of relatives of the disappeared to the OMP and their increasing demand for an international truth and justice mechanism.